Uganda : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; and a Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Uganda's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The program for 2002/03-2004/05, which could be supported by a new PRGF arrangement, aims to increase real GDP growth to about 6 1\2 percent a year on average, while holding annual inflation at about 3 1\2 percent. Monetary and exchange rate policies will focus on maintaining stability in light of sizable sterilization operations. The authorities will rely on market-based monetary instruments and will adhere to a flexible exchange rate policy.